Diversidade genética em Coffea arábica no cerrado brasileiro - Silva, Cyntia Meiry da (2015)
The coffee has importance in several segments, from social, economic to the cultural, and Brazil is the largest producer and exporter. The aim of this study was to evaluate the growth rate of 16 Arábica coffee genotypes (Coffea arabica) in the Brazilian Cerrado. The experiment was established in Morrinhos in Goiás State, with the spacing of 3x1m between plants. The design was a randomized block design with four replications; each experimental unit consists of five plants. Traits recorded length of reproductive branches, length of orthotropic branches, number of nodes of reproductive branches and number of nodes of orthotropic branches. The vegetative growth rates varied seasonally throughout the evaluation period. Set the exponential not linear model, and the quality of the model fit quantified by determining coefficients (R2), adjusted determination coefficient (), information Akaike (AIC) and the criterion Bayesian (BIC) information. It was concluded that it is possible to obtain the genotypes adapted climatic conditions of the Brazilian cerrado, with highest growth periods befitting rain and mild temperature. Presumably, the Catucaí 2 SL genotypes and Yellow Catuaí IAC 62, have characteristics that facilitate future studies of breeding for adaptation to water stress situations since they have shown minor variations in growth rates during the dry season.